Mental illness stigma and suicidality: the role of public and individual stigma. (6th December 2016) - Oexle, N.; Waldmann, T.; Staiger, T.; Xu, Z.; Rüsch, N.
Abstract : Aims: Suicide rates are increased among unemployed individuals and mental illness stigma can contribute to both unemployment and suicidality. Persons with mental illness perceive negative attitudes among the general public and experience discrimination in their everyday life (=public stigma components) potentially leading to self-stigma and anticipated discrimination (=individual stigma components). Previous research found evidence for an association between aspects of mental illness stigma and suicidality, but has not yet clarified the underlying pathways explaining how different stigma components interact and contribute to suicidal ideation. Method: Public and individual stigma components and their association with suicidal ideation were examined among 227 unemployed persons with mental illness. A path model linking public stigma components (experienced discrimination, perceived stigma) with suicidal ideation, mediated by individual stigma components (anticipated discrimination, self-stigma), was examined using structural equation modelling within Mplus. Results: Our sample was equally split in terms of gender, on average 43 years old and about half reported no suicidal ideation during the past 30 days. In bivariate analyses all stigma components were significantly associated with suicidal ideation. In the path model and controlling for symptoms, the association between experienced discrimination and suicidal ideation was fully mediated by anticipated discrimination and self-stigma. Perceived stigma's contribution to suicidal ideation was fully mediated by anticipated discrimination, but not by self-stigma. Conclusions: In general, programmes addressing multiple stigma components seem to be most effective in improving suicide prevention. Besides interventions targeting negative attitudes and discriminating behaviours of the general public, programmes to support persons with mental illness in coping with perceived and experienced stigma could improve suicide prevention. Future studies should test the short- and long-term effects of such interventions on suicidality and further investigate the role of stigma coping (e.g. secrecy) and emotional consequences (e.g. hopelessness and loneliness) for the association between stigma components and suicidality.